2008
DOI: 10.1007/s00221-008-1295-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma-decanolactone on seizures induced by PTZ-kindling in mice

Abstract: Gamma-decanolactone is a monoterpene compound, and its psychopharmacological evaluation in mice revealed that it has a dose-dependent effect on the central nervous system, with hypnotic, anticonvulsant, and hypothermic activity. The aim of the present study was to investigate the effect of gamma-decanolactone on pentylenetetrazole (PTZ)-kindling in mice. Phenobarbital, an antiepileptic drug, was also tested for the purpose of comparison. After the behavioral procedures had been undertaken, the animals were kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…They also compared the anticonvulsant activities of linalool enantiomers in PTZ, PTX, and MES models and demonstrated that (R)‐(‐)‐linalool was more potent than its enantiomeric form . The administration of γ‐decanolactone at a dose of 0.3 g/kg showed anticonvulsant properties and antiepileptogenic effects in the PTZ‐kindling model, which could also decrease the DNA damage in brain tissue both at 0.1 and 0.3 g/kg . Isopulegol, the product by cyclization of citronellol, seems to interact with a different target.…”
Section: Medicinal Compounds With Antiepileptic/anticonvulsant Activimentioning
confidence: 99%
“…They also compared the anticonvulsant activities of linalool enantiomers in PTZ, PTX, and MES models and demonstrated that (R)‐(‐)‐linalool was more potent than its enantiomeric form . The administration of γ‐decanolactone at a dose of 0.3 g/kg showed anticonvulsant properties and antiepileptogenic effects in the PTZ‐kindling model, which could also decrease the DNA damage in brain tissue both at 0.1 and 0.3 g/kg . Isopulegol, the product by cyclization of citronellol, seems to interact with a different target.…”
Section: Medicinal Compounds With Antiepileptic/anticonvulsant Activimentioning
confidence: 99%
“…Several studies describe its validity and application to study seizure, underlying the course of seizure and testing of anticonvulsant drugs. Kindling refers to a phenomenon in which generalised seizures are developed following repeated administration of subconvulsive electrical or chemical stimuli due to progressive intensification of seizure activity (Ali et al 2005;de Oliveira et al 2008). Kindling induced by PTZ is extensively used as a laboratory model of human partial complex epilepsy (Mason and Cooper 1972;Corda et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy is one of the commonest neurological disorders of the brain, affecting approximately 1% of the population worldwide (Dhir et al 2005;de Oliveira et al 2008). The pathogenesis of neuronal damage in response to seizure has been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Gama-decanolactone is a monoterpene that acts on the central nervous system as anticonvulsant and hypnotic [211]. Gama-decanolactone has neuroprotective effect against seizures induced by isoniazid and 4-aminopyridine, but not by picrotoxin.…”
Section: Gamma-decanolactonementioning
confidence: 99%